Analisis Kualitas Pelayanan Swiss-Belhotel Borneo Samarinda - Ahyar M. Diah; Amiril Azizah; Aigo Dias (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2020)
Service Quality Analysis of Swiss-Belhotel Borneo Samarinda. “The purpose of this study is to analyze, prove and describe the comparison between expectations and services quality performance of Swiss-Belhotel Borneo Samarinda. The type of observation used was quantitative with sample of 114 respondents. The analytical tool used the Validity Test, Reliability Test, Importance Analysis - Performance Analysis Cartesian’s Diagram and Paired T test. Data collection methods are using questionnaires. The data processing method uses  SPSS Software Version 17 for Windows. Based on the results of observations stated that there is a significant difference between expectations and service quality performance. This can be seen from the significant level of 0,000 <0.05 which means that there is a difference between expectations and quality performance of Swiss-Belhotel Borneo Samarinda customers